Impacts of educommunication in basic education and its contribution to teacher practice (Research, Society and Development, 2019)
The present study aims to analyze the impacts of education on teaching-learning in basic education, with emphasis on contributions to teaching practice. In this context, we highlight the educommunication, a practice that integrates education and communication, acting as an active methodology, capable of qualifying teaching practice and teaching learning. To do so, we sought to conceptualize educommunication; describe BNC guidelines; and to point out the contributions of educomunicative actions in the school. The light of the understandings of chosen authors and the National Curricular Common Base sought to elucidate the theme. The present study is of a qualitative nature, and the research method is a bibliographical review, based on the concepts of basic authors on educommunication, and education. In view of the above, it is concluded that many are the contributions of educommunication to innovation teaching and qualification of teaching practice.